Advantages and disadvantages of methods of routing of part-load consignment - Shytiy, M.I. (ХНУ ім. В. Н. Каразіна, 2012)
The article considers the advantages and disadvantages of routing of part-load consignment’s methods and determination of a rational route of load dispatch.
В статье рассматриваются преимущества и недостатки способов транспортировки мелкой отправки груза, и определение рационального маршрута распределение загрузки.
Keywords: rational route; load dispatch; method